Financial deepening and economic growth nexus in Nigeria: Supply-leading or demand-following? - Tari Moses Karimo; Oliver Ejike Ogbonna (Economies, 2017)
This paper examined the direction of causality between financial deepening and economic growth in Nigeria for the period 1970-2013. The study adopted the Toda-Yamamoto augmented Granger causality test and results showed that the growth-financial deepening nexus in Nigeria follows the supply-leading hypothesis. This means that it is financial deepening that leads to growth and not growth leading financial deepening. Among other things, the study recommended that policy efforts should be geared towards removing obstacles that undermine the growth of credit to the private sector, and must restore investors' confidence in the stock market operations.
Keywords: O16; O43; 330; financial deepening; economic growth; supply-leading hypothesis; Toda-Yamamoto augmented Granger causality